2009
DOI: 10.1186/1471-2156-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in the VKORC1 gene of wild rats and mice – a response to 50 years of selection pressure by warfarin?

Abstract: Background: Coumarin derivatives have been in world-wide use for rodent pest control for more than 50 years. Due to their retarded action as inhibitors of blood coagulation by repression of the vitamin K reductase (VKOR) activity, they are the rodenticides of choice against several species. Resistance to these compounds has been reported for rodent populations from many countries around the world and poses a considerable problem for efficacy of pest control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
214
3
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(227 citation statements)
references
References 27 publications
8
214
3
2
Order By: Relevance
“…Specifically, only 10 and 14 polymorphic synonymous and non-synonymous SNPs, respectively, were observed in the original data on SNP variation in the Norway rat [7]. Synonymous and non-synonymous divergent sites, however, were not observed (Additional file 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, only 10 and 14 polymorphic synonymous and non-synonymous SNPs, respectively, were observed in the original data on SNP variation in the Norway rat [7]. Synonymous and non-synonymous divergent sites, however, were not observed (Additional file 1).…”
Section: Resultsmentioning
confidence: 99%
“…possible R. rattus or R. rattus -like) species origin in the published data [7]. Questionable origin of SNPs was judged based on the results of phylogenetic analysis (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rost et al reported that HEK293 cells which overexpressed mutated VKORC1 (Tyr139Cys) had lower VKOR activity than that of wild-type cells, even in the absence of warfarin [12]. However, activity of the mutant VKOR was not inhibited by warfarin.…”
Section: Discussionmentioning
confidence: 99%